Enhanced surface interaction of water confined in hierarchical porous polymers induced by hydrogen bonding - Silletta, Emilia Victoria (2016)
Hierarchical porous polymer systems are increasingly applied to catalysis, bioengineering, or separation technology because of the versatility provided by the connection of mesopores with percolating macroporous structures. Nuclear magnetic resonance (NMR) is a suitable technique for the study of such systems as it can detect signals stemming from the confined liquid and translate this information into pore size, molecular mobility, and liquid−surface interactions. We focus on the properties of water confined in macroporous polymers of ethylene glycol dimethacrylate and 2-hydroxyethyl methacrylate [poly- (EGDMA-co-HEMA)] with different amounts of cross-linkers, in which a substantial variation of hydroxyl groups is achieved. As soft polymer scaffolds may swell upon saturation with determined liquids, the use of NMR is particularly important as it measures the system in its operational state. This study combines different NMR techniques to obtain information on surface interactions of water with hydrophilic polymer chains. A transition from a surface-induced relaxation in which relaxivity depends on the pore size to a regime where the organic pore surface strongly restricts water diffusion is observed. Surface affinities are defined through the molecular residence times near the network surface.